Organisasi Islam dan Pengembangan Hukum Islam di Indonesia - Fitriyani Fitriyani (Al-Ulum, 2010)
This paper discusses about Islamic organizations and its influence on the formation and development of Islamic law in Indonesia. The idea to incorporate Islamic law into the reality of the lives of the people of Indonesia is in line with the call for reform of Islamic law which arises in most Mulsim countries since the early twenty century. Institutional and constitutional reforms at the level of religious organizations such as Muhammadiyah, Nahdatul Ulama (NU), and the Islamic Union (Persis), which are often regardd as the modern movement of Islamic organizations in Indonesia.